2019
DOI: 10.1177/1559325819878537
|View full text |Cite
|
Sign up to set email alerts
|

Astaxanthin Ameliorates the Lipopolysaccharides-Induced Subfertility in Mouse via Nrf2/HO-1 Antioxidant Pathway

Abstract: The endotoxin lipopolysaccharide (LPS) exists in human semen, which is associated with reduced sperm quality. Studying the LPS-impaired spermatozoa motility and viability, and discovering effective therapeutic treatments have crucial importance. The time-course and dose–response experiments were performed to optimize the treatment dose and time of astaxanthin and LPS on mouse spermatozoa motility and viability. Sperm kinetics and morphology, reactive oxygen species production, in vitro fertilization, and devel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…Interestingly, Ytrestøyl et al (2021) also observed a modulation of hmox1 in liver, which in this case, revealed an up-regulation in salmon fed Ax. Nevertheless, based on our results, Ax would therefore impact redox balance also through heme-oxygenase-related pathway (Niu et al 2018;Wang and Zhuang 2019). Until now, no available data or literature have described possible mechanisms of Ax supplementation on the decrease of lipid peroxidation-induced ferroptosis.…”
Section: Ax Effect In Liver Of Post-smolt Salmon + Ax Vs − Axmentioning
confidence: 59%
“…Interestingly, Ytrestøyl et al (2021) also observed a modulation of hmox1 in liver, which in this case, revealed an up-regulation in salmon fed Ax. Nevertheless, based on our results, Ax would therefore impact redox balance also through heme-oxygenase-related pathway (Niu et al 2018;Wang and Zhuang 2019). Until now, no available data or literature have described possible mechanisms of Ax supplementation on the decrease of lipid peroxidation-induced ferroptosis.…”
Section: Ax Effect In Liver Of Post-smolt Salmon + Ax Vs − Axmentioning
confidence: 59%
“…Moreover, sperm motility increased from 64.40% to 76.23% in the 0–100 mg/kg ASTA-treated group ( P < 0.05). It has been previously demonstrated that sperm viability, total motility, and sperm kinematic parameters increase after ASTA treatment in mice [ 29 ]. A recent study also showed similar results that ASTA can improve post-thawed rooster sperm motility and kinetic parameters, including total motility, progressive motility, VAP, VSL, and LIN.…”
Section: Resultsmentioning
confidence: 99%
“…18 Besides, astaxanthin improves the lipopolysaccharidescaused subfertility of the mouse through Nrf2/HO-1 antioxidant pathway. 19 It is also reported that melatonin attenuates acute kidney I/R injury in diabetic rats by activating SIRT1/Nrf2/HO-1 pathway. 20 Nevertheless, the association between Apelin and Nrf2 in renal I/R injury in diabetic rats has never been explored yet.…”
Section: Introductionmentioning
confidence: 98%